Analysis of assessments at the Department of Clinical Cancer Genetics by cancer site and the importance of genetic findings in treatment planning - Nina Zavrl; Simona Hotujec; Srdjan Novaković; Stegel Vida; Mateja Krajc (Onkologija)
Introduction: The Institute of Oncology Ljubljana (IOL) provides genetic assessment for cancer patients who require test results for treatment planning and whenever there is a risk of a hereditary cancer syndrome. In this study, we aimed to analyse the trend of referrals of cancer patients and to assess the pathogenic / likely pathogenic variant (PV/LPV) detection rate in tested individuals according to family history. Methods: In the Department of Clinical Cancer Genetics, IOL, we performed data analysis using descriptive statistical methods and the Microsoft Excel tool. It was based on the number of referrals, patients’ family history data and their genetic test results for germline PV/LPV, focusing on specific cancer site (breast, ovaries, pancreas, and prostate) between 01/01/2020 and 30/06/2024. Results: In a period of 4.5 years, 4,252 patients were referred for genetic counselling, in particular breast cancer patients (3,074). On average, it took 4.3 years from cancer diagnosis to germline genetic testing. 16.5% of all patients tested were diagnosed with germline PV/LPV. Germline PV/LPV were mostly found in ovarian cancer patients (25.2%), followed by pancreatic cancer patients (16.2%), breast cancer patients (16.2%), and prostate cancer patients (11.1%). PV/LPV were most frequent in the genes BRCA1/2. The percentage of patients with a positive family history who tested positive was 19.5%, whereas the percentage of patients with a negative family history was 12.4%. Conclusion: The survey proves the importance of germline genetic testing for cancer patients and their relatives. In fact, 16.5% of patients tested positive for germline PV/LPV and the results were used for treatment planning and prevention. Therefore, it would be reasonable to consider introducing universal genetic testing for certain cancer patients in a safe clinical setting and to be able to identify all those at higher cancer risk.